Mie resonances in the spectrum of spontaneous parametric down-conversion - Santiago-Cruz, Tomás; Fedotova, Anna; Sultanov, Vitaliy; Weissflog, Maximilian; Younesi, Mohammadreza; Staude, Isabelle; Pertsch, Thomas; Setzpfandt, Frank; Chekhova, Maria V. (Optics InfoBase Conference Papers, 2021)
We report on the first-time generation of biphotons via spontaneous parametric down-conversion driven by Mie-type resonances in subwavelength metasurfaces. The measured biphoton spectrum reveals that emission predominantly occurs at the resonant wavelength of the metasurface.
CRIS-Team Scopus Importer:2021-12-03